Evangelism to the Tugutil Ethnic in Halmahera, North Maluku through the Implementation of Contextual Theological Models - Mawikere, Marde Christian Stenly; Hura, Sudiria; Wagiu, Meily Meiny; Ole, Fitria Fransisca (Institut Agama Kristen Negeri Manado, 2023)
This article describes the implementation of contextual theology models as transculturation contextualization of the evangelism to the Tugutil ethnic in Halmahera, North Maluku. The research was carried out using a qualitative ethnographic type approach built by literature studies on elements in local theology which include the inculturation of belief in God, man, sin and salvation. The purpose of this research is to formulate models of contextual theology that are relevant to the Tugutil ethnicity by utilizing their local theology. The results of this study show that there are elements of local theology of the Tugutil people who are